Incorporating narrative repair in the treatment of avoidant personality disorders: A case in point. Issue 5 (3rd May 2021) - Lind, Majse; Simonsen, Sebastian; Dunlop, William L.
Abstract: Avoidant personality disorder (AvPD) is characterized by multiple struggles, including shyness, feelings of inadequacy, and hypersensitivity to interpersonal judgments. Research indicates that people with AvPD also show disturbances in narrative identity, which is an internal and evolving story created about the personal past, present, and presumed future. Here, the novel Guide for Narrative Repair (GNaR) recently developed by (Thomsen et al., 2020) is introduced as a potentially useful tool to help people with AvPD in crafting more adaptive narrative identities. The guide is brought to life via a case study analysis of Adam, a male outpatient suffering from AvPD. Consistent with the GNaR, disturbances in Adam's storied self are brought to light and ways to facilitate his narrative repair are proposed. We conclude with implications related to the case as well as the potential narrative turn in AvPD treatment.